1999
DOI: 10.1097/00005176-199902000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in Children with Celiac Disease: Prevalence and Clinicopathologic Features

Abstract: Prevalence and clinical expressivity of H. pylori infection is not increased in children with celiac disease. The clinicopathologic pattern of the infection is not specifically influenced in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 12 publications
3
36
0
3
Order By: Relevance
“…We found no positive anti-H. pylori-IgG among the sera from the children with celiac disease identified by the mass screening study [8], which is in agreement with the results of an Italian study of 81 children with celiac disease [22].…”
Section: Discussionsupporting
confidence: 90%
“…We found no positive anti-H. pylori-IgG among the sera from the children with celiac disease identified by the mass screening study [8], which is in agreement with the results of an Italian study of 81 children with celiac disease [22].…”
Section: Discussionsupporting
confidence: 90%
“…This finding was supported by further studies conducted by Luzza et al in 1999 [15] and Aydogdu et al in 2008 [7]. However, Diamanti et al reported that patients with CD have a significantly lower prevalence of H. pylori infection compared with controls in 1999 [16].…”
Section: Discussionmentioning
confidence: 61%
“…The prevalence of Hp infection among 28 CD patients and in patients without CD was 82% and 86.2% respectively. The difference is not statistically significant, according to previous studies by Diamanti et al and Luzza et al that showed a difference in terms of prevalence not statistically significant [27,28,29]. In addition there was no relation between gastritis and severity of mucosal damage in CD.…”
Section: Resultsmentioning
confidence: 74%